What Do Clinicians Who Deliver Maternity Services Think Patient-Centered Care Is and How Is That Different for Vulnerable Women? A Qualitative Study. (2nd December 2018) - Adams, Ted; Sarnak, Dana; Lewis, Joy; Convissar, Jeff; Young, Scott S.
Abstract : Background . Patient-centered care is said to have a myriad of benefits; however, there is a lack of agreement on what exactly it consists of and how clinicians should deliver it for the benefit of their patients. In the context of maternity services and in particular for vulnerable women, we explored how clinicians describe patient-centered care and how the concept is understood in their practice. Methods . We undertook a qualitative study using interviews and a focus group, based on an interview guide developed from various patient surveys focused around the following questions: (i) How do clinicians describe patient-centered care? (ii) How does being patient-centered affect how care is delivered? (iii) Is this different for vulnerable populations? And if so, how? We sampled obstetricians and gynecologists, midwives, primary care physicians, and physician assistants from a health management organization and fee for service clinician providers from two states in the US covering insured and Medicaid populations. Results . Building a relationship between clinician and patient is central to what clinicians believe patient-centered care is. Providing individually appropriate care, engaging family members, transferring information from clinician to patient and from patient to clinician, and actively engaging with patients are also key concepts. However, vulnerable women did not benefit from patient-centered care without first having some of their nonmedical needs met by their clinician. Discussion . Most providers did not cite the core concepts of patient-centered care as defined by the Institute of Medicine and others.